Investigation of dose-dependent effects of berberine against renal ischemia/reperfusion injury in experimental diabetic rats - Kumas, Meltem; Esrefoglu, Mukaddes; Karatas, Ersin; Duymac, Nurcihan; Kanbay, Songul; Ergun, Ilyas Samet; Uyuklu, Mehmet (Soc Espanola Nefrologia Dr Rafael Matesanz, 2019)
Background: Ischemia-reperfusion injury causes various severe morphological and functional changes in diabetic patients. To date, numerous antidiabetic and antioxidant agents have been used for treatment of the disease-related changes. Objectives: We aimed to examine effective therapeutic doses or doses of berberine against renal ischemia/reperfusion injury (IRI) in a streptozotocin (STZ)-induced diabetic rat model by histopathological and biochemical analysis. Methods: Thirty male Sprague Dawley rats were treated with STZ injection for the development of diabetes, and divided into the following groups: STZ-induced diabetic group (STZ); IRI-induced diabetic group (STZ + IRI); 50 mg/kg berberine (BRB) treated diabetic group after inducing IRI (STZ + IRI + BRB1); 100 mg/kg BRB treated diabetic group after IRI (STZ + IRI + BRB2); 150 mg/kg BRB treated diabetic group after IRI (STZ + IRI + BRB3). Bilateral renal ischemia model was applied for 45 min, then reperfusion was allowed for 14 days in STZ-induced diabetic rats. Renal injury was detected histopathologically. Blood urea nitrogen (BUN), creatinine and lactate dehydrogenase (LDH) levels were measured in serum using the ELISA method. Total antioxidant status (TAS) and total oxidant status (TOS) of renal tissue was studied by spectrophotometric assay. Oxidative stress index (OSI) was calculated as TOS-to-TAS ratio. Tumor necrosis factor alpha (TNF-alpha), C-reactive protein (CRP), Na+/K+-ATPase (sodium pump), and Ca2+-ATPase (calcium ATPase) enzyme levels were measured in tissues using the ELISA method. Anti-apoptotic Bax and pro-apoptotic Bcl-2 protein levels were detected by Western blot analysis. All data were evaluated statistically. Results: The highest histopathological score was detected in the STZ + IRI group compared to the other group. BRB administration at the doses of 100 mg/kg and 150 mg/kg markedly improved renal injury. BUN and creatinine levels significantly increased in the STZ + IRI group compared to the STZ group (p <0.001). 100 mg/kg and 150 mg/kg BRB administration significantly decreased those levels (p < 0.01). The highest TOS and the lowest TAS levels were detected in the STZ + IRI group (p < 0.001). IRI markedly aggravated inflammation via increasing levels of TNF-alpha and CRP (<0.001), and caused apoptosis via inducing Bcl-2 protein, and suppressing Bax protein (p < 0.001). BRB administration at the doses of 100 mg/kg and 150 mg/kg showed anti-oxidant, anti-inflammatory and anti- apoptotic effects (p < 0.01). The LDH enzyme, was used as a necrosis marker, was higher in the STZ + IRI group than other groups. BRB administration at all of the doses, resulted in the decline of LDH enzyme level (p < 0.001). Ca2+-ATPase and Na-(+)/K+-ATPase enzyme activities decreased in the STZ + IRI group compared to the STZ group (p < 0.001), while BRB administration at the doses of 100 mg/kg and 150 mg/kg significantly increased those of enzyme activities, respectively (p < 0.05). Conclusion: Ischemia with diabetes caused severe histopathological and biochemical damage in renal tissue. The high doses of berberine markedly improved histopathological findings, regulated kidney function via decreasing BUN and creatinine levels, and rearranged intercellular ion concentration via increasing Na-(+)/K+-ATPase and Ca2+- ATPase levels. Berberine showed anti-oxidant, anti-apoptotic, and anti-inflammatory effects. According to these data, we suggest that berberine at the doses of 100 and 150 mg may be used as a potential therapeutic agent to prevent renal ischemic injury. (C) 2019 Sociedad Espanola de Nefrologia. Published by Elsevier Espana, S.L.U. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0).
Keywords: Renal ischemia/reperfusion injury; Berberine; Histopathology; Oxidative stress; Apoptosis; Inflammation